Migration discourse: a cognitive-pragmatic vantage point - Shevchenko, Iryna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
This article focuses on the English-language migration discourse and aims to develop its methodology through the lens of cognitive pragmatics and cognitively oriented critical discourse analysis. The analysis is underpinned by understanding of discourse against a social, pragmatic, and cognitive background, which postulates the unity of cognitive and pragmatic aspects of migration discourse. This paper focuses on the 2024 USA presidential election as a case study. First, I studied the discourse-generating concept of migrant represented in Donald Trump’s utterances by lexemes, word-combinations, and cognitive metaphors. Then with the help of critical discourse analysis framework I singled out discourse strategies of migration discourse in the Republican Party Platform and in Harris – Trump presidential debate. In the 2024 USA presidential election campaign, the written migration discourse of the Republican Party sought to evoke negative emotions and included populist content. I argue that in his speeches at public events, Donald Trump often generated dramatization, both verbally and non-verbally, and engaged in negative campaigning concerning the issues of migrants and migration. Migration discourse that involved negative campaigning and evoked negative emotions towards migrants yielded high voters engagement. Negative, exaggerated, and sensationalized style of argumentation in migration issues is a strategic tool of Donald Trump’s political discourse, intentionally meant to reach the voters both rationally and subconsciously. Republican migration discourse is ethno- and culturally specified; its strategies bear the features of xenophobic ethno-cultural stereotypes that are underpinned by cognitive ‘immigrants-as-home-invaders’ scenario based on discursive narrowing of the conceptual space of migrant as compared to that of citizen.